121‐story Shanghai Center Tower foundation re‐analysis using a compensated pile foundation theory. (17th May 2013) - Tang, Yongjing; Zhao, Xihong
SUMMARY This paper attempts to re‐analyze the piled raft foundation in the Shanghai Center Tower as a fully compensated foundation using a hybrid method of superstructure–foundation interaction and other methods. Some cases were used to the applicability of the methods. The deformation analysis is divided into four parts: (a) Part 1: heave due to the weight of the excavated soil, (b) Part 2 : recompression due to the dead load of the structure, (c) Part 3 : recompression due to the live load of the structure and (d) Part 4 : settlement due to the constant load. Load acting on the top of the pile group and load sharing between the raft and the piles are also considered. The results are also compared in detail with the measured ones. In addition, research based on earth pressure theory was conducted to determine how to reduce or control the overturning moment caused by wind. Finally, this paper suggests that the Shanghai Center Tower, which is currently under construction, can have more than 121 stories by improving the design, which will also result in great investment savings. Copyright © 2013 John Wiley & Sons, Ltd.